Hubungan Pengetahuan Ibu Dengan Pemberian Asi Eksklusif Di Rs Ibu Dan Anak Dwi Sari Lubuklinggau Tahun 2024 - Putri, Detri Arifah; Annisa, Kintan; Yovita Sari, Lezi (Utami Publisher, 2025)
The need of nutritional is very important in the process of growth and development of infants. This requirement can be fulfilled by exclusive breastfeeding. Exclusive breastfeeding gives to infants 0-6 months without any additional food. Impact if infant is not given an exclusively breastfed are antibody decrease and it cause the baby to be susceptible to diseases such as diarrhea, cramps, caries effects, jaundice, and other chronic diseases. The purpose of this study was to analyze the relationship between maternal knowledge with exclusive breastfeeding in infants 6-12 months in Puskesmas Pertiwi Makassar. This type of research was an observational analytic with cross sectional approach. The sampling method used was a non-probability by apply an accidental sampling approach and a sample were 50 respondents. Collecting data used the questionnaires. The results based on statistical test Chi Square with alternative test Fisher Exact Test, p = 0.000 <α = 0.05, which meant p <α can conclude alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected, which meant there was a relationship of knowledge mother with exclusive breastfeeding in infants 6-12 months RS Ibu dan Anak Dwi Sari LubukLinggau Year 2024.